Identifi cation of security of the hydrographic network of agricultural territories against diff use pollution - Nataliya V. Kirpichnikova; Irina A. Vishnevskaya; Yulia D. Chernenko (Водное хозяйство России: проблемы, технологии, управление)
Traditionally, water protection programs are developed in a long term and are oriented, mainly to reduce wastewater point sources of pollution, practically ignoring the whole class of uncontrolled sources of diff use pollution. Th ese uncontrolled sources of diff use pollution are characterized by complex dynamics depending on many factors and hydro/meteorological conditions. On the example of the formation of a biogenic fl ow of agricultural territories, the article discusses the methodological approaches to the estimation of diff use sources of pollution from the position of long-term dynamics, identification of territories with maximum anthropogenic load and security of river catchments.